Blunt Abdominal Trauma: An Evaluation At Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2014)
Blunt Abdominal Trauma (BAT) is a common paediatric surgical problem in Bangladesh. This retrospective study was carried out from July 2010 to June 2013 to evaluate the management of patients with BAT in the department of Paediatric Surgery of Chittagong Medical Hospital. Hospital records were analyzed regarding mechanism of injury, clinical presentations, investigations, treatment and follow up. This study was aimed at observing present management of BAT and advocate further improvement. The age range was up to 12 years. Total number of patients studied was 48, with male female ratio of 3:1. 9 children were < 5 years of age and 39 children were > 5 years of age. Common mechanism of injury were road traffic accident (56.25%) and fall from a height (31.25%). 33 patients presented within 24 hours (68.75%) and 15 presented after 24 hours (31.25%). 5 patients (10.65%) presented with shock and 34 patients (70.83%) had signs of peritonitis. 36 patients (75%) were treated conservatively and surgical intervention was required in 12 cases (25%). After one month, 1 patient presented with Pancreatic pseudocystand 2 patient developed intestinal obstruction.JCMCTA 2014 ; 25 (2) : 26-30